Assessment of Gastric Accommodation by SPECT - Hong, Sung Pyo (Journal of neurogastroenterology and motility, 2010)
The reproducibility of 99mTc-pertechnetate single photon emission computed tomography (SPECT) for measurement of gastric accommodation in healthy humans: Evaluation of the test results performed at the same time and different time of the day KCI Citation Count: 0